Teaching Foreign Languages through Visual Aids: The Learning Potential of Art Images - Pioli, Marco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study aims to promote the mindful use of visual aids in language teaching. In particular, after illustrating a brief theoretical framework, it presents two teaching activities experimented at university level with the objective of investigating the learning potential which art images, especially from painting, can have in teaching Italian as a foreign language. The positive results achieved in students’ participation and learning confirmed the initial hypotheses, underlining the cognitive and motivational advantages which visual elicitation and art inputs can provide to language acquisition.